Wireless measurement of orthodontic forces in invisible aligners - Siyu Wang; Bingxin Xu; Xiaokang Wang; Xinfang Li; Bangzheng Pu; Gui Chen; Jianmin Han; Shengzhao Xiao; Yubo Fan; Jiebo Li (Medicine in Novel Technology and Devices, 2024)
Invisible orthodontic treatment is an effective form of malocclusion treatment favored in recent years. The magnitude of its orthodontic force has a crucial impact on the outcome of the treatment and has gained a high level of clinical interest. However, there are very few explorations of in vivo measurements of orthodontic force, and existing studies are limited to a large number of couplings, which are inconvenient for clinical use. In this work, we developed a wireless flexible measurement system that allows quantitative measurement of the orthodontic force of an invisible aligner on a dental model. The system is wireless, tiny, flexible, fast responding, and has a range suitable for the range of orthodontic forces. We show the difference in the orthodontic force applied to different tooth positions and the difference in the orthodontic force applied to different positions of the same tooth. In addition, the system can evaluate the mechanical differences between aligners of different brands and materials as well as the deviation of fabrication results. This system provides a test tool and evaluation method for future real-time assessment of clinical orthodontic forces.